ANTIDIABETIC ACTIVITY OF ETHANOLIC EXTRACT OF EUGENIA POLYANTHA WIGHT LEAF FROM INDONESIA IN DIABETIC RAT WISTAR STRAIN INDUCED BY ALLOXAN - Sutrisna, Em (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The purpose of this study is to determine the antidiabetic activity of 96% ethanolic extract of Eugenia polyantha wight leaves. Methods: Twenty-five male Wistar rats were divided into 5 groups. Group I was negative control (aquabidest),group II was positive control (Glibenclamide 0.45 mg/kg), group III, IV, and V were treated by the 96% ethanolic extract of leaves of Eugenia polyantha wight with doses of 312,5; 625; and 1250 mg/kg respectively. Before the treatment, All rats were induced byÂ alloxan with dose of 150 mg / kg by intra peritoneal. On 3rd day after induction, rats with blood glucose level> 200 mg/dL were treated by drugs or extract appropriate to the group. On 10th day, after blood sampling, all rats were killed and the pancreas were taken for histophatology examination. The blood glucose level on 10th day was tested byÂ Kruskall- Wallis test followed by the Mann-Whitney with confidence levelÂ 95%. Results: Â The 96% ethanolic extract of leaves of Eugenia polyantha wight at doses of 312.5 mg/kg, 625 mg/kg and 1250 mg/kg body weight can reduce blood glucose levels in rat induced by alloxan. The 96% ethanolic extract of Eugenia polyantha wight at dose of 1250 mg/kg body weight potentially regenerate LangerhansÂ cell Â induced by alloxan. This extract has potentials as antidiabetic agent Conclusion: This study shows that the 96% ethanolic extract ofÂ Eugenia polyantha wight can be developed as an antidiabetic agent